Thermo-hydraulic performance of connected single-phase natural circulation loops characterized by two different inner diameters. (June 2021) - Misale, Mario; Bocanegra, Johan Augusto; Marchitto, Annalisa
Abstract: In this paper, an experimental study regarding the natural circulation in connected vertical rectangular loops is presented. Typically, the geometry of the natural circulation loops (NCL) is rectangular or toroidal and the analysis is focused on the thermo-hydraulic behaviour of a single working loop. In this study, a new approach referred to several NCLs simultaneously operated was investigated. In the experimental setup, the lower heated sections of the NCLs are connected. The tests were carried out by varying the internal diameter of the loops to investigate the influence of the mutual interaction between two adjacent NCLs. The data were analyzed by the modified Vijayan's correlation showing a good agreement. A simple relationship is proposed to normalize the data both in terms of inner tube diameter and heat sink temperature. The results obtained with two NCLs characterized by different internal diameters could be considered as the first attempt to try optimizing several connected NCLs.